FOOD SAFETY AND HACCP SYSTEM IN THE PHYSALIS CONFITURE PRODUCTION - Ravshanbek Alibekov; D. Sylvain Dabadé; Klara Urazbayeva; Gulbagi Orymbetova; Zaripa Alibekova (Academic Scientific Journal of Chemistry, 2019)
The identification of hazards and the principles of the food safety management system are considered. Within the processing of the fruit and berry raws, the jam and confiture production technologies could assume Critical Control Points that will influence the final product safety. In the productionof Physalis confiture with a lemon, a sugar and apple pectin,by taking into account the principles of the HACCP system,the technological processes are analyzed. Physalis as a natural antioxidant has a high nutritional value and useful features in medicine. In this regard it is important to keep all Physalis benefits in the confiture production. Each technological process step by step analyzed, andprerequisites of the Critical Control Points were determined. The most important production stages are: reception and sorting, cleaning and sterilization. For the avoiding of the negative factors,monitoring system, control and corrective actions on the base of the HACCP / MS ISO 22000:2018 Food safety management systems standard are offered.